Comprehensive analysis of putrescine metabolism in A thaliana using GWAS, genetic risk score, metabolic modelling and data mining - Schwarzerová, Jana; Bartoň, Vojtěch; Walther, Dirk; Weckwerth, Wolfram (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2023)
Polyamines are known to be functionally involvedin plant responses to stress conditions. Despite a large amount ofphysiological and genetic data, the mode of action of polyamines,especially putrescine, at the molecular level still remains unclear.An increasing number of studies point to a role of putrescine instress defense of plants due to influencing the formation of reactiveoxygen species (ROS) in cellular stress conditions. Moreover,putrescine has been found to modulate abscisic acid (ABA)biosynthesis at the transcriptional level in response to lowtemperature, revealing a novel mode of action of polyamines asregulators of hormone biosynthesis. This study presents a newholistic approach towards the analysis of putrescine metabolismusing genome-wide association studies and the calculation ofgenetic risk scores extended by Boolean analysis in metabolitesnetwork as well as data mining from available databases andliterature. It can lead to a better understanding of biologicalprocesses involved in adaptation of plants to environmentalchanges.
Keywords: Diversification; GWAS; Genetic Risk Score,The 1001 Genomes Project; Reactive Oxygen Species